How to build an effective research network: lessons from two decades of the GARNet plant science community. (8th September 2020) - Parry, Geraint; Benitez-Alfonso, Yoselin; Gibbs, Daniel J; Grant, Murray; Harper, Andrea; Harrison, C Jill; Kaiserli, Eirini; Leonelli, Sabina; May, Sean; McKim, Sarah; Spoel, Steven; Turnbull, Colin; et al.
Abstract: Successful collaborative research is dependent on excellent ideas and innovative experimental approaches, as well as the provision of appropriate support networks. Collaboration requires venues, infrastructures, training facilities, and, perhaps most importantly, a sustained commitment to work together as a community. These activities do not occur without significant effort, yet can be facilitated and overseen by the leadership of a research network that has a clearly defined role to help build resources for their community. Over the past 20 years, this is a role that the UKRI-BBSRC-funded GARNet network has played in the support of the UK curiosity-driven, discovery-led plant science research community. This article reviews the lessons learnt by GARNet in the hope that they can inform the practical implementation of current and future research networks. Abstract : Lessons learnt from the activities of the GARNet research network in their support of the global plant science community are discussed.